ANALISIS PENGARUH KEPERCAYAAN, KEKUATAN MEREK (BRAND EQUITY), KEPUASAN DAN KUALITAS LAYANAN TERHADAP - Yuniar Eko Pramono (JURNAL MANAJEMEN, 2015)
This study aims to determine Is the confidence, the strength of the brand (brand equity), satisfaction and service quality significantly influence consumer purchasing decisions lightweight steel roof truss (Pryda) Raka Mitra Jaya CV and analyze which of the dominant variable influencing consumer purchasing decisions. The population in this study is a customer CV. Raka Mitra Jaya taken as many as 63 respondents using simple random sampling technique sampling technique based on respondents who had ever bought a product steel roof truss (Pryda) CV Raka Mitra Jaya. Based on the research results, obtained the following regression equation: Y = 0,136X1 + 0,177X2 + 0,107X3 + 0,062X4. Based on statistical data analysis, indicators in this study are valid and are reliable variables. In the analytical testing validity, reliability and regression analysis. Calculation or testing the hypothesis by using statistical computer program SPSS 17.00. Individual sequence of each variable is the variable most influential brand power with a regression coefficient of 0.177, confidence with a regression coefficient of 0.136, satisfaction with a regression coefficient of 0.107 and quality service with a regression coefficient of 0.062. This research is the dominant variable is the strength of the brand, with the results of the regression of 0.177. The research results that all independent variable positive and significant impact on purchasing decisions through F test. Keywords: confidence, strength of the brand (brand equity), satisfaction, quality service and purchasing decisions